2019
DOI: 10.1007/s00223-019-00548-7
|View full text |Cite
|
Sign up to set email alerts
|

Regional Changes in Density and Microarchitecture in the Ultradistal Tibia of Female Recruits After U.S. Army Basic Combat Training

Abstract: Musculoskeletal injuries, such as stress fracture, are responsible for over 10-million lost-duty days among U.S. Army Soldiers. During Basic Combat Training (BCT), an 8-to 10-week program that transforms civilians into Soldiers, women are four times more likely than men to sustain a stress fracture. In this work, we performed high-resolution peripheral quantitative computed tomography scans on the ultradistal tibia of 90 female recruits [age = 21.5 ± 3.3 (mean ± standard deviation) years] before the start of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Recent studies have examined the effect of exercise on bone microarchitecture. A 2019 study showed that among 90 female army recruits, eight weeks of basic combat training led to significant increases trabecular bone density driven by increases in trabecular thickness, and site-specific increases in cortical bone density, driven by increased cortical thickness, in regions of greatest loading [61]. Although many studies have reported equivocal or negative effects for exercise interventions in postmenopausal women, a recent systematic review [62] and meta-analysis [63] concluded that medium and high-intensity exercises-but not low intensity exercises-are effective at improving bone in the lumbar spine and hip in this population.…”
Section: Prospective Interventionsmentioning
confidence: 99%
“…Recent studies have examined the effect of exercise on bone microarchitecture. A 2019 study showed that among 90 female army recruits, eight weeks of basic combat training led to significant increases trabecular bone density driven by increases in trabecular thickness, and site-specific increases in cortical bone density, driven by increased cortical thickness, in regions of greatest loading [61]. Although many studies have reported equivocal or negative effects for exercise interventions in postmenopausal women, a recent systematic review [62] and meta-analysis [63] concluded that medium and high-intensity exercises-but not low intensity exercises-are effective at improving bone in the lumbar spine and hip in this population.…”
Section: Prospective Interventionsmentioning
confidence: 99%
“…(1) The physical activity that occurs during basic combat training (BCT), a rigorous period at the beginning of a soldier's career, causes adaptive bone formation in the tibia, which is a common location for stress fractures. (2)(3)(4)(5) Adaptive bone formation may confer increases in bone strength (6) and fatigue resistance, (7) which could have important implications for stress fracture prevention. (8) During military training, females have a threefold greater risk of stress fractures than males.…”
Section: Introductionmentioning
confidence: 99%
“…Basic combat training (BCT) is performed at the beginning of military life, lasts 12 weeks, and aims to transform trainees from civilians to soldiers [1,2]. In the case of military universities such as the Hellenic Army Academy, first-grade cadets participate in BCT [3][4][5].…”
Section: Introductionmentioning
confidence: 99%